The Influence of Rewards, Incentives, and Internal Communication on Employee Performance with Job Satisfaction as a Mediating Variable - Rakhmat Indra Wiryawan; Susanti Widhiastuti (Masterpiece, 2026)
Employee performance is a crucial factor in achieving organizational goals; therefore, understanding the factors that influence it is essential. This study aims to analyze the impact of rewards, incentives, and internal communication on employee performance, with job satisfaction serving as a mediating variable, within the Order-to-Cash Department of PT OCS Global Services. A quantitative approach was employed, utilizing a census method covering 55 employees. Data were collected via Likert-scale questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that rewards, incentives, and internal communication have a positive and significant impact on job satisfaction. Regarding direct effects, incentives and job satisfaction significantly influence employee performance, whereas rewards and internal communication do not. Furthermore, job satisfaction significantly mediates the impact of rewards and incentives on performance but does not mediate the impact of internal communication. These findings suggest that enhancing employee performance requires effective incentive management and the improvement of job satisfaction as a key organizational factor. This study offers novel contributions in several respects. First, it integrates financial factors (rewards and incentives) and non-financial factors (internal communication) into a single research model incorporating job satisfaction as a mediating variable—an approach relatively limited in prior research. Second, the study focuses on the specific context of the Order-to-Cash (O2C) Department, characterized by administrative, process-driven work focused on financial transaction accuracy, thereby providing a fresh perspective on employee performance studies within the facility services sector. Third, the study sheds light on inconsistencies in previous research findings by demonstrating that not all organizational factors directly influence performance; rather, some operate through the psychological mechanism of job satisfaction. Consequently, this study contributes to enriching organizational behavior models by making them more contextual and comprehensive.